2021
DOI: 10.1007/s43545-021-00194-7
|View full text |Cite
|
Sign up to set email alerts
|

How do teachers’ perceptions of climate change vary in terms of importance, causes, impacts and mitigation? A comparative study in Bangladesh

Abstract: Since climate change education is an integral element in the increasingly urgent global approach to solving the problem of climate change, understanding perceptions of climate change among teachers in different academic institutions could play a significant role in how and to what extent institutions address the need to educate learners on this subject, specifically, and participate in other climate change mitigation strategies, in general. This study, therefore, examines teachers’ perceptions of climate chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…In Bangladesh, studies show that factors such as experiences of EWEs in one’s own locality ( Haq and Ahmed, 2019 ; Chowdhury et al, 2021 ; Ahmed et al, 2022 ), age, gender, education, religion, marital status, occupation, income, size of landholdings, and exposure to mass media are correlated with and explain variations in perceptions about climate change ( Anik and Khan, 2012 ; Huda, 2013 ; Haq and Ahmed, 2017 ). However, not all factors are equally influential or statistically significant, and their influence differs from one study area to another ( Haq and Ahmed, 2017 ; Ahmed and Haq, 2019 ).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…In Bangladesh, studies show that factors such as experiences of EWEs in one’s own locality ( Haq and Ahmed, 2019 ; Chowdhury et al, 2021 ; Ahmed et al, 2022 ), age, gender, education, religion, marital status, occupation, income, size of landholdings, and exposure to mass media are correlated with and explain variations in perceptions about climate change ( Anik and Khan, 2012 ; Huda, 2013 ; Haq and Ahmed, 2017 ). However, not all factors are equally influential or statistically significant, and their influence differs from one study area to another ( Haq and Ahmed, 2017 ; Ahmed and Haq, 2019 ).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Gashu et al (2020), in their study in Ethiopia, argue that demographic, socio-economic, institutional, and physical factors contribute to different perceptions of green infrastructure. Other studies associated with perceptions of climate change (e.g., Haq and Ahmed, 2017;Chowdhury et al, 2021) have also examined the socio-demographic and economic context of such perceptions in Bangladesh. Priego et al (2008), in their study of urban residents of surveyed areas in Chile, Germany, and Spain, observed that participants from these areas shared a strong interest in nature, especially the local environment.…”
Section: Socio-demographic and Economic Factors Influencing The Perceptions Of Ugssmentioning
confidence: 99%
“…Peoples' previous experiences, values, beliefs, histories, and local cultures significantly influence their perceptions of the benefits of UGSs (e.g., physical, social, mental, economic, climate change mitigation, and ecosystem services) and their use of UGSs contributes to an understanding of their environmental behavior (Petrişor and Petrişor, 2020). In studies of perceptions of climate change in Bangladesh among on university students (Haq and Ahmed, 2020), on school and college teachers (Chowdhury et al, 2021), and on indigenous people (Ahmed and Atiqul Haq, 2019), a wide range of factors influencing peoples' perception was found. The divergent contexts in which the studies reviewed were conducted are likely to explain differences in public perceptions of urban green space.…”
Section: Divergence Of Socio-cultural Contextsmentioning
confidence: 99%
“…To achieve an effective climate action especially at the individual or local levels, people would need to be knowledgeable about climate change and also have science-based https://jurnaldidaktika.org perceptions about the phenomenon. This is because research shows that knowledge and perceptions impact strategies developed to address climate change (Chowdhury et al, 2021;Scannell & Gifford, 2013). However, different factors shape climate change knowledge, perceptions as well as action; some of which are education, economic/social status, gender, religious beliefs, affiliation and attendance, etc.…”
Section: Introductionmentioning
confidence: 99%